CAUSAL FACTORS AFFECTING THE HYPERTENSION PREVENTION BEHAVIORS OF AMONG AT RISK PEOPLE IN THE HEALTH REGION 4 MINISTRY OF PULBIC HEALTH - Srilatham, Tipsukhon (Journal of Buddhist Anthropology, 2021)
The purpose of this research was to study Health literacy, Motivation to prevention and social support that is the causal factors affecting the preventive behaviors of hypertension at risk people in The Health Region 4 Ministry of Public Health. The samples 650 people were aged 35–59 years who were screened for high blood pressure risk and were at-risk of hypertension. The sample were obtained by employing the multistage random sampling method. Data collection was done by using 5 scale with questionnaires. The statistics used for data analysis were percentage, mean, percentage mean, standard deviation and path analysis was done by using program AMOS. The results showed that model of the causal factors affecting the hypertension preventive behaviors developed was harmonized with the empirical data: χ2 = 129.853, df = 108 χ2/df = 1.202, p = 0.075, CFI = 0.998, GFI = 0.981, AGFI = 0.960, TLI = 0.960 NFI = 0.987, RMSEA = 0.018, RMR = 0.014, The factors in regard to Health literacy, Motivation to prevention and social support were found to significant influence directly on hypertension preventive behaviors. (r2 = 0.28, 0.65 and 0.24 respectively) p < 0.01 All variables in the model were able to explain the variance of preventive behaviors hypertension by 71.5%. Recommendations from this research. The results of the research should be used to formulate policies and plans to Hypertension preventive behaviors. with an emphasis on Health literacy, Protection Motivation, Social support and Healthy lifestyle. Encourage health workers to work with communities allowing people in the community to participate fully in health promotion activities under the management system by linking network partners.